Informasi Banjir di Aceh Tamiang: Citizen–Generated Content Versus Klarifikasi Pemerintah - Armelia Agustina; Annisa Fitra Laila; Erick Prasyawan; Rahmanita Ginting (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
This study aims to analyze the framing of the government and citizen-generated content on flood information in Aceh Tamiang and compare the construction of meaning, responsibility, and handling recommendations built by the two actors in the digital communication space. The method used is qualitative research with Robert Entman's framing analysis design, using data in the form of TikTok content consisting of official government clarifications and public content in the November-December 2025 period, which is collected through non-participatory observation and documentation, then categorized based on the function of problem definition, causal diagnosis, moral assessment, and solution recommendations. The results show that government framing tends to emphasize stability, perception control, and institutional legitimacy by reducing crises as controlled situations, while citizen-generated content displays the reality of humanitarian crises, inequality of handling, delayed responses, and social and ecological damage as the center of meaning, thus forming a strong counter-narrative in the digital public space. The comparison of the two framing shows the battle of meaning between the narrative of state stability and the direct experiences of survivors that affect audience reception and public trust. This study recommends the repositioning of government disaster communication towards a more transparent, empathetic, and participatory approach, strengthening risk communication based on field experience by disaster management agencies, and the development of advanced research that integrates framing analysis with audience reception studies and digital platform dynamics.